Strategi Mahasiswa dalam Mengelola Citra Diri di Instagram: Studi Naratif 5 Mahasiswa Program Studi Hubungan Masyarakat Universitas Indonesia - Sasta Intan Nafisa; Efina Engelica Putri; Jovanka Tarisa; Ryandika Christian Nugroho (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of social media has transformed the way individuals construct and present their social identities, particularly among university students. Instagram has evolved beyond a mere visual content-sharing platform into a strategic arena where individuals actively shape and manage their self-image before digital audiences. This study aims to examine students' strategies in presenting self-image on the front stage, to explore the role of back stage in maintaining image consistency, and to understand how students perceive the difference between their online and offline selves. A qualitative approach with a narrative inquiry method was employed, involving five active students from the Public Relations Study Program at Universitas Indonesia, class of 2024, selected through purposive sampling. Data were collected through in-depth interviews, documentation, and literature review, with source triangulation applied for data validation. The analysis was conducted through Erving Goffman's dramaturgical perspective, encompassing four key concepts: front stage, back stage, impression management, and audience segregation. The findings reveal that self-image management on Instagram is a deliberate and strategic process, manifested through rigorous content curation, multi-account ownership as a means of separating public and private spaces, and the archiving of posts as a corrective image mechanism. All informants exhibited tension between the desire for authentic self-expression and the performative demands of digital social norms. Instagram was assigned diverse meanings, ranging from a social medium and personal branding tool to a canvas of personal identity. This study affirms the enduring relevance of dramaturgical theory in digital contexts and implies the need for digital literacy education.